Bimodal-grained high-strength nickel-base ODS alloy fabricated by mechanical alloying and hot extrusion. (March 2021) - He, Wuqiang; Liu, Feng; Tan, Liming; Huang, Lan; Nie, Yan; Wang, Guowei; Zhan, Xin; Qin, Zijun
Abstract: Two nickel-base oxide dispersion strengthened (ODS) alloys with uniform and bimodal distribution of grains size were fabricated by mechanical alloying (MA) and hot extrusion (HEX) in this work. The effects of grain size distribution on the tensile properties from ambient temperature to 1000 °C was comprehensively studied. The results of microstructure characterization indicated that high density of nanosized particles and dislocation were formed in both nickel-base ODS alloys. Moreover, the strength of nickel-base ODS alloy was mainly derived from grain boundary strengthening, dislocation strengthening and precipitation strengthening. Comparing to the alloy with uniform grains size, the bimodal-grained nickel-base ODS alloy owned prior combination of strength and ductility.